The influence of training, subjective norms, and self-efficacy on entrepreneurial passion and intention of engineering students - Trieu Khoa Nguyen; Ninh Gia Nguyen (International Journal of Evaluation and Research in Education (IJERE), 2026)
Entrepreneurial passion and intention are critical drivers of innovation and economic development. However, empirical studies have primarily focused on business and social science students and have not yet extensively studied engineering students. This study examines how entrepreneurship training influences entrepreneurial passion and intention among engineering students, focusing on the mediating roles of subjective norms and entrepreneurial self-efficacy (ESE). Using a cross-sectional survey design, data were collected from 368 final-year engineering students at the Industrial University of Ho Chi Minh City, Vietnam, and analyzed with partial least-squares structural equation modeling (PLS-SEM). Importance–performance map analysis (IPMA) was also employed to identify the most influential predictors. Results reveal that entrepreneurship training enhances both subjective norms and ESE, which significantly fosters entrepreneurial passion, while entrepreneurial passion strongly predicts entrepreneurial intention. Mediation analyses confirmed that subjective norms and ESE partially mediate the effect of entrepreneurship training on entrepreneurial passion. Theoretically, the study extends social cognitive theory (SCT) by demonstrating how personal and contextual factors jointly shape entrepreneurial passion and intention. Practically, the findings highlight the need for entrepreneurship programs in engineering education to emphasize experiential learning, confidence building, and supportive social environments that strengthen entrepreneurial mindsets.